Biolegal guidelines with a classical natural law approach for the regulation of a palliative care law in Peru - Gonzales Montenegro, Katherinne Jhoana (2022)
Given the current situation and based on the worldcontext, a reflection and legal solution is provided, from a iusnaturalist approach to the problem of the care of the chronically ill, rescuing the value of dignity in their last stage of life; for which the institution of palliative care is analyzed. It has been verified that, at the national level, Law 30846 has been in place since 2018:"Lawthat creates the National Palliative Care Plan for Oncological and Non- Oncological Diseases"; and with the Technical Document "National Plan of Palliative Care for Oncological and Non-Oncological Diseases in Peru 2021-2023”, however, there is no specific law on palliative care in Peru. Therefore, the present investigation; provide a bio-legal approach to the dignified treatment of the chronically ill in Peru. In this sense, it is proposed as a general objective: to establish guidelines based on a classic iusnaturalist position for the regulation of palliative care, with a biolegal approach, in favor of a dignified treatment of the patient in Peru. To achieve this objective, qualitative, descriptive and interpretative research was pursued.